MULTIKULTURALISME DALAM SISTEM PENDIDIKAN AGAMA ISLAM: Problematika Pendidikan Agama Islam di Sekolah - Suyatno, Suyatno (ADDIN, 2013)
MULTICULTURALISM IN ISLAMIC EDUCATION SYSTEM: PROBLEMS OF ISLAMIC EDUCATION IN SCHOOLS. Education aimed at shaping attitudes and behavior towards the civilized man. An education system that only emphasizes the transfer of knowledge, making education is no longer meaningful and a positive effect on learners. Education is not touching the side of humanism that develops an attitude of pluralism as a foundation of multiculturalisms thought. Model of religious education would only create learners abdullah which are only godly individually. Understanding pluralism and multiculturalism has become a commodity in politics that will continue to roll in the realm of national education including Islamic religious education which is an integral part of the national education system. The governments policy regarding the application of curriculum of KTSP which necessitates the provision of education oriented to potential of regional and local cultural values. This policy can not be separated from the awareness of the figures and leaders of this country that the Indonesian nation is very diverse and heterogeneous. Therefore, it is impossible to build this country withot considering of the values of plurality and multicultural in society.